Altered of apoptotic markers of both extrinsic and intrinsic pathways induced by hepatitis C virus infection in peripheral blood mononuclear cells - Albertoni, Guilherme [UNIFESP] (2012)
Background: Chronic hepatitis C (CHC) has emerged as a leading cause of cirrhosis in the U. S. and across the world. To understand the role of apoptotic pathways in hepatitis C virus (HCV) infection, we studied the mRNA and protein expression patterns of apoptosis-related genes in peripheral blood mononuclear cells (PBMC) obtained from patients with HCV infection.Methods: the present study included 50 subjects which plasma samples were positive for HCV, but negative for human immunodeficiency virus (HIV) or hepatitis B virus (HBV). These cases were divided into four groups according to METAVIR, a score-based analysis which helps to interpret a liver biopsy according to the degree of inflammation and fibrosis. mRNA expression of the studied genes were analyzed by reverse transcription of quantitative polymerase chain reaction (RT-qPCR) and protein levels, analyzed by ELISA, was also conducted. HCV genotyping was also determined.Results: HCV infection increased mRNA expression and protein synthesis of caspase 8 in group 1 by 3 fold and 4 fold, respectively (p < 0.05). in group 4 HCV infection increased mRNA expression and protein synthesis of caspase 9 by 2 fold and 1,5 fold, respectively (p < 0.05). Also, caspase 3 mRNA expression and protein synthesis had level augumented by HCV infection in group 1 by 4 fold and 5 fold, respectively, and in group 4 by 6 fold and 7 fold, respectively (p < 0.05).Conclusions: HCV induces alteration at both genomic and protein levels of apoptosis markers involved with extrinsic and intrinsic pathways.